The results of study of promising red clover varieties in competitive varietal trial - M. N. Gripas; E. G. Arzamasova; E. V. Popova (Аграрная наука Евро-Северо-Востока, 2019)
The article presents the results of study of promising diploid and tetraploid red clover varieties, differed by ripening time, sowed in 2016 in competitive varietal trial at two-year cutting mode of grass-stand use. In the conditions of Kirov region, there was carried out a comprehensive assessment of varieties according to the following biological and production indicators: winter hardiness, duration of growing season, plant and grass-stand height, leafiness, productivity of dry mass by cuttings and in total for two years of use, protein and fiber content, yield of raw protein and digestible protein, resistance to root rot. In each group of ripeness, the best varieties have been identified. They combined protein productivity, winter hardiness (72.3-94.0 %) and resistance to root rot: early tetraploid population SGPFT-170-2 which significantly exceeded the standard (st.) Kudesnik in the yield of raw protein by 0.49 t/ha and digestible protein by 0.355 t/ha, medium-resistant to root rot, with less root system damage compared to the standard by 5.6% in the first year of use (1 y. u.) and 3.3% in the second year of use (2 y. u.); diploid early variety GPF-54-2, which significantly exceeded st. Dymkovsky by 0.391 t/ha in the yield of raw protein in total for two years of use and showed resistance to root rot in the 1 y. u.; diploid late varieties SGP-105 and GPR-36-2, which provided significant additions to st. Kirovsky 159 in the yield of raw protein (+1.216 and +0.964 t/ha) and digestible protein (+0.918 and +0.726 t/ha), combining fodder productivity with resistance to root rot in the 1 y. u. and average resistance in the 2 y. u. (st. Kirovsky 159 is susceptible).Conflict of interest: the authors stated that there was no conflict of interest.